How the EU can move to a higher growth path: some considerations - Horst Siebert (Institut für Weltwirtschaft (IfW), 2001)
In the current slowdown in Europe, the United States and Japan, policy makers are vexed by the question when a recovery will come. This is the wrong question. The issue should be how a higher growth path can be reached in the long run, i.e., how the potential growth rate of our economies can be increased from the supply side.
Keywords: 330; Wachstumspolitik; Angebotsorientierte Wirtschaftspolitik; Wirtschaftspolitische Beratung; EU-Staaten